Etiological, Clinical, and Epidemiological Characteristics of Acute Viral Gastroenteritis in an Adult Population in a Tertiary Level Hospital in Spain - Sara Herranz-Ulldemolins; Anna Sellarès-Crous; Miriam J. Álvarez-Martínez; M. Eugenia Valls; Marta Aldea Novo; Anna Vilella Morató; Laura Rodriguez; Mireia Navarro; Roser Vendrell; Josep Barrachina; Miguel J. Martínez; M. Ángeles Marcos (Infectious Diseases and Therapy)
Abstract Introduction Acute gastroenteritis (AGE) represents a significant global health burden, with enteric viruses being a leading cause of gastroenteritis worldwide. Despite advances in diagnosis and treatment, there are limited data on adults seeking care due to AGE of viral etiology. This study aimed to describe the etiological, clinical, and epidemiological characteristics of viral AGE in adult patients presenting for medical consultation in a tertiary hospital over a 2-year period. Methods A retrospective cross-sectional study was conducted, with 8886 stool samples from 8356 adult patients presenting acute diarrhea between January 2021 and December 2022. A molecular real-time RT-PCR panel was used to screen for common bacterial, parasitic, and viral pathogens. Clinical and demographic data were collected, and statistical analysis was performed to evaluate possible associations. Results Enteric viruses constituted 10.3% (307 cases) of all AGE of known etiology, with norovirus being the predominant pathogen (196, 63.8%), followed by rotavirus (82, 26.7%) and adenovirus (29, 9.4%). The different viruses showed a distinct seasonal predominance. Coinfection with other microorganisms was common. Most cases exhibited a self-limiting course. Mortality and hospitalization rates were high in patients with higher comorbidity indices, mainly in individuals with immunosuppression. Conclusions Viruses are an important cause of acute gastroenteritis in adults presenting for medical consultation. The new multiplex molecular tests with high sensitivity and specificity allow early differential diagnosis in AGE. It is therefore necessary to identify which special populations particularly with higher comorbidity indices, would benefit from the implementation of these techniques, to guide decision-making related to appropriate treatments and avoid unnecessary interventions.